Migration-related determinants of health-related quality of life of persons with direct migration background in Germany: a study based on the German Socio-Economic Panel - Grochtdreis, Thomas; König, Hans-Helmut; Dams, Judith (Frontiers in Public Health, 2024)
Persons with a direct migration background made up a share of around 17% of the total German population in the year 2020. Not much is known about migration-related determinants of health-related quality of life (HrQoL) of persons with direct migration background. This study aimed to analyze the associations between HrQoL, sociodemographic, and migration-related characteristics of persons with direct migration background in Germany.Methods. The sample of this study was based on four waves (2014, 2016, 2018, and 2020) of the migration samples (M1 and M2) of the German Socioeconomic Panel (SOEP). The SF-12 was used to measure HrQoL using its mental (MCS) and physical (PCS) component summary scores. Missing information was replaced by multiple imputation by chained equations with predictive mean matching. Associations between HrQoL and sociodemographic and migration-related characteristics were examined using multilevel mixed-effects linear regressions.Results. The mean MCS and PCS scores of persons with direct migration background (n = 4124) were 51.81 and 51.57, respectively. Being born in Russia was associated statistically significantly with a lower PCS score compared with non-east European and American/Oceanic countries. A longer period since migration to Germany was negatively associated with both MCS and PCS scores (both with p < 0.01). A steady relationship before migration was associated with a higher MCS score (+0.69, p = 0.017). Not feeling German and experiencing disadvantages due to origin were negatively associated with the MCS (both with p < 0.001). The oral ability in the German language was positively associated with the PCS score (p < 0.05).The time since migration to Germany, and the relationship status before migration may be determinants of HrQoL of persons with a direct migration background. Furthermore, connectedness with Germany, disadvantages due to origin and oral ability in the German language, representative of integration in Germany, can be potential determinants of HrQoL. Thus, integration of persons with migration background is crucial for their mental and physical HrQoL.